Women Consumer Behavior at Coffee Shop Bandar Lampung - Azzahro, Witri; Ali, Suprihatin; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2022)
This study describes the behavior of female consumers in coffee shops in the city of Bandar Lampung and the factors behind it. This type of research is descriptive with a qualitative approach. Data were collected by means of documentation, observations, and in-depth interviews with 15 female consumer informants. Data was taken by purposive sampling technique and data analysis was carried out by triangulation of sources. Based on the results of research and data analysis, it shows that female consumers in coffee shops carry out work activities, do assignments, relax and hang out with close relatives (kongko). The four activities are influenced by two factors, namely psychological factors which include motivation, perception, experience, beliefs and attitudes and cultural factors which include culture and social class. The implications of this research for businessmen are to provide educative games such as uno cards, uno blocks, chess, and snakes and ladders, magazines or light reading books, seat arrangements that are not too close to the position facing the wall, as well as exploring the taste of coffee that improve the mood to unwind after activities.